ग्रेगरी, पिसकोर र धामी–झाँक्री संस्कृतिको अध्ययन - Karki, Dinesh (Dhaulagiri Journal of Sociology and Anthropology, 2023)
This paper describes the interaction and understanding with Professor Gregory G. Maskarinec and his study in Jajarkot, Nepal.